2003
DOI: 10.1359/jbmr.2003.18.11.2002
|View full text |Cite
|
Sign up to set email alerts
|

Climbing Exercise Increases Bone Mass and Trabecular Bone Turnover Through Transient Regulation of Marrow Osteogenic and Osteoclastogenic Potentials in Mice

Abstract: To investigate the relationship between the effects of bone turnover and bone marrow cell development in bone cells, we developed a mouse voluntary climbing exercise model. Climbing exercise increased bone volume and transient osteogenic potential of bone marrow. This model would be suitable for investigating the mechanistic roles of mechanical loading. Introduction:The relationship between bone mass gain and local bone formation and resorption in mechanically loaded bone is not well understood. Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
85
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 39 publications
12
85
1
1
Order By: Relevance
“…The effect of r-irisin, essentially mimicking the effect of mechanotransduction (25)(26)(27), thus allows bone to become structurally more efficient for bending and torsion. Indeed, both mouse (28)(29)(30) and rat (31-34) models have collectively shown positive associations between exercise and increased bone size and bone mass.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of r-irisin, essentially mimicking the effect of mechanotransduction (25)(26)(27), thus allows bone to become structurally more efficient for bending and torsion. Indeed, both mouse (28)(29)(30) and rat (31-34) models have collectively shown positive associations between exercise and increased bone size and bone mass.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise-based mouse [1][2][3][4][5] and rat [6][7][8][9] models have almost universally shown a link between exercise and increased bone formation, resulting in increased bone size and bone mass and maintenance or increase of mechanical properties, thus supporting Wolff's law [10]. We recently demonstrated that 21 consecutive days of moderate intensity running, considerably shorter than most exercise models, significantly increased structural post-yield deformation in the tibial diaphyses of male C57BL6/129 mice [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the effect of short exercise periods on bone mineral content in rodent models (Kodama et al, 2000;Mori et al, 2003;Plochocki et al, 2008). However, the documentation regarding the effect of long-term exercise and timing of exercise is limited (Hoshi et al, 1998;Jarvinen et al, 2003;Pajamaki et al, 2003).…”
Section: Introductionmentioning
confidence: 99%